Wave Dispersion and Attenuation in Viscoelastic Split Hopkinson Pressure Bar. (1998) - Cheng, Z.Q.; Crandall, J.R.; Pilkey, W.D.
Abstract : A viscoelastic split Hopkinson pressure bar intended for testing soft materials with low acoustic impedance is studied. Using one-dimensional linear viscoelastic wave propagation theory, the basic equations have been established for the determination of the stress—strain—strain rate relationship for the tested material. A method, based on the spectral analysis of wave motion and using measured wave signals along the split Hopkinson pressure bar, is developed for the correction of the dispersion and attenuation of viscoelastic waves. Computational simulations are performed to show the feasibility of the method.